2015
DOI: 10.1097/won.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Study of the Effects of 2 Fecal Management Systems on Incidence of Anal Erosion

Abstract: In this randomized comparative effectiveness research study, there was no difference in the incidence of anal erosion between groups. Purchasing decisions cannot be made based on differences in general product characteristics postulated to influence likelihood of anal erosion. Results regarding balloon water volume, mucosa pressure generated, and anal erosions require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…3,[11][12][13][14][15][16] FMSs are also cost-saving, with few to no complications reported in most series. 3,5,17 However, there is a lack of high-quality data describing experiences with FMS use, because the majority of relevant literature consists of small cohorts with <50 patients. [11][12][13][14][15][16] Despite promising initial reports, there have been cases of severe rectal ulceration, fistula formation, and hemorrhage associated with FMS use, highlighting the need to identify risk factors for complications.…”
Section: Incidencia Y Caracterización De Las Complicaciones Rectales ...mentioning
confidence: 99%
See 1 more Smart Citation
“…3,[11][12][13][14][15][16] FMSs are also cost-saving, with few to no complications reported in most series. 3,5,17 However, there is a lack of high-quality data describing experiences with FMS use, because the majority of relevant literature consists of small cohorts with <50 patients. [11][12][13][14][15][16] Despite promising initial reports, there have been cases of severe rectal ulceration, fistula formation, and hemorrhage associated with FMS use, highlighting the need to identify risk factors for complications.…”
Section: Incidencia Y Caracterización De Las Complicaciones Rectales ...mentioning
confidence: 99%
“…3,11–16 FMSs are also cost-saving, with few to no complications reported in most series. 3,5,17 However, there is a lack of high-quality data describing experiences with FMS use, because the majority of relevant literature consists of small cohorts with <50 patients. 11–16…”
mentioning
confidence: 99%
“… 8 13 Moreover, studies have suggested that prolonged IBC use can lead to anal erosion and anal sphincter dysfunction in some patients. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%